Narratives of resistance: political allegory in post-reform Indonesian novels - Refai (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Post-Reform Indonesian literature reflects a complex negotiation between memory, power, and freedom, where political allegory becomes a medium of cultural resistance and moral reflection. Objective: This study aims to examine how post-1998 Indonesian novels construct narratives of resistance through political allegory, metaphorical discourse, and ideological positioning. Method: Using a qualitative interpretive method that integrates Narrative Analysis (Labov & Waletzky), Allegorical-Symbolic Analysis (Frye), and Critical Discourse Analysis (Fairclough), ten novels published between 1998 and 2020 were analyzed as this research corpus. Results: The findings reveal three major patterns: first, economic metaphors such as “corruption = disease” and “capital = monster” dominate the symbolic critique of power; second, ideological metaphors articulate plural resistance—especially feminist and religious reformist stances—through dialogic narrative structures; and third, lexical metaphors like “fire,” “blood,” and “silence” establish an evolving language of dissent that connects trauma, identity, and justice. Implication: These results imply that metaphor functions not merely as ornamentation but as a cognitive and ideological structure that shapes how Indonesian readers and writers imagine democracy and moral recovery. Novelty: This study enriches literary and cultural discourse by showing how allegory operates as a sociopolitical grammar of resistance in post-authoritarian Indonesia.